Enhancement of ultrafast conductivity in surface-passivated GaAs - Lloyd-Hughes, J; Merchant, S; Fu, L; Tan, H; Jagadish, C; Castro-Camus, E; Johnston, M (Optical Society of America, 2007)
Optical-pump/terahertz-probe spectroscopy and terahertz emission spectroscopy were used to measure the conductivity and surface electric field change resulting from passivating the surface of GaAs. An enhanced terahertz radiation generation from passivated photoconductive antenna was observed. © 2006 Optical Society of America.